Pelatihan Pembuatan Pellet Ternak Babi Fase Starter bagi Kelompok Tani Tungku Mose di Kabupaten Manggarai NTT - Dalle, Nautus Stivano; Sikone, Hilarius Yosef; Djami Adi, Defiyanto (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to improve the knowledge and skills of farmer group members by providing education and practical training on pellet making for starter phase pig livestock. This activity was carried out at the Mose Furnace Farmers Group, Manggarai Regency, East Nusa Tenggara (NTT) which was attended by 21 group members. This activity was carried out with FGD (Focus Group Discussion) and provided a pretest and postest to measure the improvement of the ability of farmer group members. The results of this community service show that there is an 80% increase in the knowledge of farmer group members about making starter phase pig pellets and skills in calculating ration formulations for pigs using trial and error methods, mixing rations, molding and drying.